Exploring the role of organizational support, and critical success factors on renewable energy projects of Pakistan. (15th March 2022) - Rasool, Samma Faiz; Chin, Tachia; Wang, Mansi; Asghar, Ali; Khan, Anwar; Zhou, Li
Abstract: This study investigates the relationship between critical success factors (CSFs), organizational support, and renewable energy project success. The critical success factors with multiple dimensions (communication, team, technical, and environmental) were used in this paper. This study adopts the questionnaire survey approach, and collects data from the construction based renewable energy projects located in Punjab Province, Pakistan, which comprised 342 valid samples. Partial least-squares structural equation modelling (PLS-SEM) was used to analyze the theoretical framework. The results confirmed that three critical success factors i.e. team factors (TF), technical factors (Tech. F), and environmental factors (EF), have a positive and significant direct relationship with project success. However, communication factors (CF) have a direct but insignificant relationship with project success. Moreover, results also confirmed the positive mediating role of organizational support between critical success factors and project success. The empirical outcomes of this study show that these four critical success factors increase the success of renewable energy projects. The outcomes also show that organizational support as a mediating variable plays a dynamic role in enhancing the tangible success of renewable energy projects. This study contributes through empirical findings in the existing knowledge base for renewable energy projects. Highlights: The study applied partial least-squares structural equation modelling. We analyzed how critical success factors influence the renewable energy projects. The study identified four critical success factors for renewable energy projects. Organizational support mediates in enhancing renewable energy projects. Critical success factors significantly improve the project success.